O Estado de Santa Catarina e o Mercosul - Gonçalves, José Correia (2009)
This thesis is intended to demonstrate how the State of Santa Catarina has been related with Mercosul, especially in the areas of foreign trade, tourism and education at university level. However, it was necessary to report the various attempts at integration with Latin America, especially in the periods that the happened the treaties, agreements, minutes, protocols, etc., in order to determine its relationship with Mercosul, still worrying to verify the main effects to the trade balance in Brazil. The methods used for this study were works of authors who wrote about the issues, research with official state and federal government, and others. The results presented help to verify that Brazil has increased so significantly their trade with Mercosul. Actually, the State of Santa Catarina has been a very important participant in the process of integration with Mercosul, by importing and exporting trade, tourism, university association, the role of the State government and many other areas